Developing a user-centered software development process - enhancing usability and customer focus. - Nimstedt, Josefin; Rodriguez, Martin (My University, 2010)
Competition among IT-companies for market shares increases daily. To win customers' trust, companies must offer high quality and user-focused solutions to an affordable cost. This master thesis focuses on changing the approach of an IT-consulting company, based on an interaction design perspective. Following a self-diagnosis through an analytical study, issues were clarified with a need of focused requirement management. An improvement strategy was applied and through its outcome, a new software development process was created, considering the early involvement of the user. A pilot study was conducted with the created process, emphasizing known methods, streamlining communication and development, in order to evaluate the new approach. It resulted in a customized process that fulfilled the company’s criteria, increasing their awareness of a user-centered process’ impact. The decision to implement the new development process still remains within the company, since their willingness as organization is a pre-requisite.
Keywords: Information Technology; Informationsteknik